Types and Function of Swear Words in Normal People Series Season One - Ni Wayan Intan Putri Widyanti (Publikasi Indonesia, 2023)
This research is an analysis of swear words used in the Normal People Series season. Language usage is more modern in the modern era, and people use swear words more frequently in their daily language. Swearing has become common in modern society. Swear words are the least preferred language, but they frequently carry a different message within their meaning. Therefore, social contact is very essential for human beings because it is the foundation to build strong connections among people in society. Therefore, to make social contact function and transmitted properly people need to have language as a means of communication. This research aims to find out the types of swear words and to describe the functions of swear words that were found in Normal People Series Season one. This research uses a qualitative method. The source data is taken from the Hulu Normal People Series Season one. The writer uses Hughe’s theory to find out the types of swear words and uses Andresson and Thrudgill's theory to find out the function of swearing used in Normal People Series Season one. The result The types and functions of Swear Words in Normal People series season one are divided into four parts. Hudges divides the types of swear words they are 38 related to the name of an animal swear words, 9 related to excrement swear words, 4 related to sex swear words, and 3 related to religion or oath swearwords.